2005
DOI: 10.1097/00002508-200503000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cognitive-Behavioral and Physical Therapy Preventive Interventions on Pain-Related Sick Leave

Abstract: Taken as a whole, this study shows that adding cognitive-behavioral intervention and cognitive-behavioral intervention and preventive physical therapy can enhance the prevention of long-term disability. There was no substantial difference in the results between the cognitive-behavioral intervention group and cognitive-behavioral intervention and preventive physical therapy group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
1
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(124 citation statements)
references
References 35 publications
2
107
1
11
Order By: Relevance
“…There is evidence that identifying patients with elevated fearavoidance beliefs and managing them accordingly may reduce fear and improve outcomes. [3][4][5][10][11][12][13][14][15][16][17][18][19][20]36,40,41,56,68 The purpose of this study was to determine the effect of adding a single-item screening variable that classified patients with elevated versus not elevated fearavoidance beliefs of physical activities on a model that predicts risk-adjusted FS outcomes.…”
Section: T T Conclusionmentioning
confidence: 99%
“…There is evidence that identifying patients with elevated fearavoidance beliefs and managing them accordingly may reduce fear and improve outcomes. [3][4][5][10][11][12][13][14][15][16][17][18][19][20]36,40,41,56,68 The purpose of this study was to determine the effect of adding a single-item screening variable that classified patients with elevated versus not elevated fearavoidance beliefs of physical activities on a model that predicts risk-adjusted FS outcomes.…”
Section: T T Conclusionmentioning
confidence: 99%
“…327f.). Bendix et al (1996); Lambeek et al (2010); Linton et al (2005); Lukinmaa (1989); Strand et al (2001); Von Korff et al (2005) ** Bendix et al (1996); Bendix et al (1998); Lambeek et al (2010); Linton et al (2005); Lukinmaa (1989); Strand et al (2005); Von Korff et al (2005) …”
Section: Das Gesundheitsproblem Das Gesundheitsproblem Und Die Folgenmentioning
confidence: 99%
“…Bei Lukinmaa (1989) wird die MBRIntervention nicht genauer beschrieben. Im Rahmen der MBR-Interventionen wird nur in zwei Studien (Bendix et al, 1996;Bendix et al, 1998;Linton, Boersma, Jansson, Svärd & Botvalde, 2005) von Schmerzedukation oder einem Training des Copings berichtet. Die Kontrollintervention ("usual care") war nur unzureichend als "normale" Versorgung durch medizinische Spezialisten in den Niederlanden (Lambeek et al, 2010), "normale" Versorgung in Dänemark (Bendix et al, 1996;Bendix et al, 1998), "normale" Versorgung in der Gesellschaft und gewöhnliche Medikation (Von Korff et al, 2005) sowie als orthopädische ambulante Intervention nach biomedizinischem Konzept (Lukinmaa, 1989) beschrieben.…”
Section: Endpunktspezifische Zusammenfassung Der Evidenzlage Und Idenunclassified
“…14,33,39,43,115,135 The fear of pain and the catastrophic vision of pain also occur in pain-free people, so these beliefs can play an important role in the development of new episodes of pain. In studies performed in subjects without low back pain, 49,71,72,120 it was observed that fear of pain increased the risk of suffering episodes of low back pain, and therefore the risk of a disability was increased. Picavet 94 performed a longitudinal study in a population of 1,571 subjects without any important illness during 6 months.…”
Section: Fear-avoidance Model In Musculoskeletal Painmentioning
confidence: 99%